The Socioeconomic Impact of Coastal Environment Changes on Fishing Communities and Adaptation Strategies - Yao-Jen Hsiao (Fishes, 2022)
Oysters are one of the main aquatic products produced in Taiwan. However, because of the gradual changes in the environment of the Waisanding Sandbar, the oyster farming environment along the coast of Chiayi is shrinking, leading to greater operational risk and uncertainty. This study adopted a three-stage method to investigate the socioeconomic uncertainty that fishing communities face regarding environmental changes and to understand the environmental risk and fishery management awareness of different stakeholders as well as their views on adaptation strategies. In-depth interviews were used in the first stage. In Stage 2, two-round focus group interviews were conducted to organize views on the environment and climate, the oyster industry and management, and adaptation strategies. In the final stage, the AHP method was adopted to analyze the opinions of different stakeholders. The results showed factors affecting environmental change, oyster industry, and management among different stakeholders as well as the cognitive differences within the corresponding adaptation strategies. Therefore, socioeconomic and ecology complexities and uncertainties should be considered for enhancing social capital and promoting risk communication, more diverse social–ecological system data to assist fishery governance, and oyster industry development and adaptation strategies.